Magnetostriction Generator as Acoustic Wave Generator for Underwater Applications - Rustamaji Rustamaji; Kania Sawitri; Mustafidz Ahdan (Faculty of Engineering, Universitas Tanjungpura, 2022)
At this time the research related to the effect of magnetostriction for underwater applications is still limited. Acoustic or sound waves are more easily propagated underwater than electromagnetic waves or light. An acoustic wave or sound can be generated by utilizing the magnetostriction effect, where this effect occurs when a rod of ferromagnetic material such as iron or nickel is magnetized and interacts with another magnetic field, resulting in vibration of the metal rod. This research aims to design and realize a magnetostriction generator as an acoustic wave generator at a frequency of 1 to 10 kHz for underwater applications, consisting of: a tuned LC oscillator circuit, and a ferromagnetic metal rod which is magnetized using a dc voltage. The results of measurements and testing of the magnetostriction generator show: (1) if it is equipped with a membrane, can work to emit an acoustic wave or sound at a frequency of ± 8.62 kHz in the air up to a distance of 15 cm without distortion with an average amplitude decrease of ± 0.648 dB for each the distance increased by 1 cm, and (2) if equipped with a membrane and enclosed in a waterproof casing, capable of transmitting the acoustic waves at a frequency of ± 8.31 kHz underwater up to a distance of 7 cm without distortion with an average amplitude decrease of ± 4.217 dB for each the distance up 1 cm. Overall the magnetostriction generator designed can work to generate and transmit the acoustic waves or sound underwater, as expected.